If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + 8 = 2 Reorder the terms: 3(4 + x) + 8 = 2 (4 * 3 + x * 3) + 8 = 2 (12 + 3x) + 8 = 2 Reorder the terms: 12 + 8 + 3x = 2 Combine like terms: 12 + 8 = 20 20 + 3x = 2 Solving 20 + 3x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 3x = 2 + -20 Combine like terms: 20 + -20 = 0 0 + 3x = 2 + -20 3x = 2 + -20 Combine like terms: 2 + -20 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 4x^2=81 | | 55=5(2x+3) | | x^2+8x=-16 | | 12(3x-2)=3(12x+4) | | 42=3(4x+2) | | y=x+45-90 | | 51-0.5p=2.5p | | -(7y+2)-(-6y-6)=-3 | | 3(2x+7)=-29+44 | | 36a^2-4=0 | | (x-6)(3x+4)=-11 | | 0=320x-.1x^2 | | 26=2(5x+3) | | 5x-2(3x+5)=32 | | 9a-3=2a+11 | | 3(5+3m)-8=88 | | 92-20=9x | | y=3x^2+6x-9 | | 138=-2+7r | | 4x+5=41 | | 30-10=5x | | 8=-2x-12 | | 6(4x-5)=2(12x+4) | | 10-6=2x | | 4+17m-1=9m+33-7m | | 3x+(-5x-(-x+3))=8x+(-5x-9) | | 15x-20= | | -6x+5=59 | | .67x+4=6x-5 | | -2=4c+14 | | 14c=269.50 | | X+12=25 |